MRI-based cerebellar volume measurements correlate with the International Cooperative Ataxia Rating Scale score in patients with spinocerebellar degeneration or multiple system atrophy. Issue 1 (December 2016) - Hara, Daisuke; Maki, Futaba; Tanaka, Shigeaki; Sasaki, Rie; Hasegawa, Yasuhiro
Abstract Background Progression of clinical symptoms and cerebellar atrophy may vary among subtypes of spinocerebellar degeneration and multiple system atrophy. The aim of this cross-sectional study was to demonstrate the relationship between the International Cooperative Ataxia Rating Scale (ICARS) score and cerebellar volume derived from magnetic resonance imaging (MRI) in a broad spectrum of Japanese patients with cerebellar ataxia. Methods A total of 86 patients with cerebellar ataxia (18 with cortical cerebellar atrophy, 34 with spinocerebellar ataxia, and 34 with multiple system atrophy) and 30 healthy subjects were studied. MRI-based cerebellar volume measurements were performed in all subjects using T1-weighted images acquired with a 1.5-T MRI scanner. The cerebellar volume/cranial anteroposterior (AP) diameter was used for statistical analysis. Results Stepwise multiple regression analyses demonstrated that cerebellar volume/cranial AP diameter and midbrain AP/cranial AP diameter were significantly associated with the total score and domain I sub-score of ICARS. We found no interactions between these two anatomical factors in the ICARS total and domain I sub-scores. The main effects of these two predictors were statistically significant both in total and domain I sub-scores (p  = 0.001 and 0.022, respectively). Conclusions Cerebellar volume and midbrain AP diameter normalized to the cranial AP diameter were significantly correlated with the ICARS total and domain I sub-scores. Further longitudinal studies are warranted to explore the role of these MRI biomarkers for predicting disease progression.